Simple and extended reproduction of fixed assets: a retrospective and current trends - N. L. Antonova; L. A. Antonov (Путеводитель предпринимателя, 2020)
The article deals with the reproduction of fixed assets. The definitions of the notion «Reproduction» of various authors are given and their analysis is carried out. Describes a simple and advanced method of reproduction, with an emphasis on the independence of the nature of the reproduction of fixed assets from the method ofdepreciation. A retrospective analysis of the development of the theory and practice of reproduction and amortization is carried out.